Representasi Sisterhood pada Film Yuni - Tansha Nastiti, Talitha; Rahardjo, Turnomo; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The high rate of early marriage in Indonesia and the existence of cases of women who are perpetrators of psychological violence against other women are the background of this research. Yuni is a film that specifically addresses the main topic of the reality of women's lives in the Serang Banten area as the main premise. This research aims to determine the representation of sisterhood in the film Yuni. The main theory used is standpoint theory supported by the concept of representation and the flow of feminist existentialism. The method used is Roland Barthes' semiotic analysis through five reading codes. This research found four forms of support provided by fellow women, namely tangible support, self-esteem support, appraisal support, and belonging support. This support takes the form of praise, advice, physical assistance, physical touch, feelings of empathy that arise towards fellow women, and acceptance between women. In this research, it was found that there are myths regarding women's self-silencing due to the existence of patriarchal culture and gender norms in society. Sisterhood is described as a value that can provide a sense of calm, happiness, comfort, feeling of acceptance and can increase women's self-confidence. However, this film also illustrates that the value of sisterhood also failed to encourage women to be able to fight against existing social constructions.